Niche divergence versus neutral processes: combined environmental and genetic analyses identify contrasting patterns of differentiation in recently diverged pine species. - Alejandra Moreno-Letelier (PLoS ONE, 2013)
Background and aims Solving relationships of recently diverged taxa, poses a challenge due to shared polymorphism and weak reproductive barriers. Multiple lines of evidence are needed to identify independently evolving lineages. This is especially true of long-lived species with large effective population sizes, and slow rates of lineage sorting. North American pines are an interesting group to test this multiple approach. Our aim is to combine cytoplasmic genetic markers with environmental information to clarify species boundaries and relationships of the species complex of Pinus flexilis, Pinus ayacahuite, and Pinus strobiformis. Methods Mitochondrial and chloroplast sequences were combined with previously obtained microsatellite data and contrasted with environmental information to reconstruct phylogenetic relationships of the species complex. Ecological niche models were compared to test if ecological divergence is significant among species. Key results and conclusion Separately, both genetic and ecological evidence support a clear differentiation of all three species but with different topology, but also reveal an ancestral contact zone between P. strobiformis and P. ayacahuite. The marked ecological differentiation of P. flexilis suggests that ecological speciation has occurred in this lineage, but this is not reflected in neutral markers. The inclusion of environmental traits in phylogenetic reconstruction improved the resolution of internal branches. We suggest that combining environmental and genetic information would be useful for species delimitation and phylogenetic studies in other recently diverged species complexes.